Effect of Advertising Exposure, Sales Promotion and Packaging towards Purchase Request of Kinder Joy to Childrens - Pudyastuti, Lintang Dwi; S,Sos, M.Si, Nurist Surayya Ulfa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Marketing activities are so exist nowaday for company profit of marketers. One of them is for brand of snacks children. The marketers are trying so hard to attract children’s attention. Moreover, children are easy targets to affected because their thought process and the logic still in the developing stages. So, all kind of marketing activities maximized its use by the marketer. Some of them such as advertising impressions on television, the addition of sales promotion or packaging on snacks. The impact arising from the strategy of marketing activities is the level of consumption of children at these snacks are high. Whereas most of that snacks are not good for their health. This study aims to determine the influence of television advertising (X1), sales promotion (X2) and packaging (X3) against the purchase request Kinder Joy to Children (Y). This study uses the theory Overall Model Of Consumer Behavior with supporting concepts from Shimp about ads and sales promotion and also from Peter and Olson about consumer behavior. Subjects were 50 students from SD N 2 Banyumanik Semarang, and non-probability sampling is obtained in the form of purposive sampling. Methods of data collection using questionnaires with data analysis statistical test multiple linear regeresi. The first hypothesis test, demonstrate the significant value of TV advertising exposure to purchase request 0,018 ( 0.05) so it can be interpreted that the variable is not significant. Based on the research results, it can be concluded that TV advertising and sales promotion affect the purchase request of Kinder Joy. These findings support the theory Overall Model Of Consumer Behavior. That is, the higher exposure to TV advertising and sales promotion, make higher demand for the purchase of Kinder Joy to children. But not for packaging because the findings were not significant and this finding is supported by the concept of Peter and Olson regarding consumer behavior.